Peningkatan Literasi dan Keamanan Digital Bagi Kreator Konten di Kota Lhokseumawe - Jafaruddin; Zahari; Masriadi; Kamaruddin; Harinawati; Asmaul Husna; Awaluddin Arifin (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service initiative aims to strengthen digital literacy and raise cybersecurity awareness among content creators and youth in Uteunkot Village, Muara Dua District, Lhokseumawe City. The location was selected as part of the 2025 community empowerment program funded through Unimal’s PNBP scheme. In today’s increasingly complex digital landscape, the need for strong literacy and security awareness is urgent particularly for groups that are highly exposed to online risiko. Young people and digital creators are among the most vulnerable to cyber threats such as phishing scams, social media account breaches, identity theft, and misuse of personal data. In Aceh, cases of cybercrime continue to rise and now affect not only the general public but also professionals such as teachers and journalists. This situation highlights the growing importance of community-level cybersecurity education, especially for rural youth who are active internet users and often produce digital content. The program is expected to enhance the skills and awareness of young people and content creators in safeguarding their digital presence, while also encouraging the formation of a local community that prioritizes responsible and secure online behavior. The training is delivered through an intensive two-day workshop, followed by online mentoring through a discussion group. To assess the participants’ progress, the program includes pre-tests and post-tests measuring improvements in their understanding of digital security